Gastrodin attenuates lithium-pilocarpine-induced epilepsy by activating AMPK-mediated PPARα in a juvenile rat model - Yang, Yanfei; Li, Yabin; Han, Jinli; Wang, Yanfen (Bioscience, biotechnology, and biochemistry, 2021)
ABSTRACT Gastrodin has shown the potential as an anticonvulsant. Epilepsy is a neurological disease with significant effects in children. In the current study, the therapeutic potential of gastrodin in handling pediatric epilepsy was explored by focusing on the AMPK/PPARα pathway. Three-week-old Sprague–Dawley rats were subjected to lithium-pilocarpine method to induce epileptic symptoms and then administrated with gastrodin. The effects of gastrodin on rats were first assessed using electroencephalogram (EEG) recording, Racine classification, Morris water maze test, and histological staining. The levels of BDNF and NGF, and the activity of AMPK/PPARα were measured. Based on the results of EEG, behavior analyses, and histological staining, epileptic symptoms were significantly alleviated by gastrodin. Moreover, the administration of gastrodin also suppressed the levels of BDNF and NGF, and activated the AMPK/PPARα pathway. In conclusion, our results demonstrated that gastrodin contributed to the alleviation of pediatric epilepsy by activating AMPK/PPARα signaling transduction. Graphical Abstract Graphical Abstract Gastrodin improves the cognitive function of juvenile epileptic rats.